Paracetamol Versus Fentanyl for Pain Control in Patients Under Extracorporeal Shockwave Lithotripsy - Abdinezhad, Ashkan; Mohaghegh Dolatabadi, Mahmoud Reza; Movaseghi, Gholamreza (Annals of Anesthesiology and Critical Care, 2018)
Background: Extracorporeal Shockwave Lithotripsy (ESWL) is a safe and noninvasive management for upper urinary tract calculi. It is potentially a painful procedure. There are different analgesic agents for pain relief during ESWL. Successful treatment depends on good management of pain. Therefore, a standard protocol is needed for administering an analgesic agent. This study was designed to compare the efficacy and side effects of paracetamol and fentanyl for pain control during extracorporeal shock wave lithotripsy. Methods: In this randomized clinical trial, 102 patients with upper urinary tract stones undergoing SWL were randomly divided to two groups. Group P received 15 mg/kg of paracetamol 10 minutes before the procedure, and group F received 1 _g/kg intravenous fentanyl three minutes before the procedure. Pain scores were assessed with the 10-score linear Visual Analogue pain Scale (VAS). The VAS scores, systolic and diastolic blood pressure, and peripheral oxygen saturation were recorded before the procedure and every 10 minutes during the ESWL. Side effects (nausea and vomiting) and satisfaction scores were recorded. Results: There were no statistically significant differences in VAS scores between the two groups, except for those at 30 minutes, at which group P showed a higher VAS value. There were less supplemental analgesia requirement and side effects in the P group compared with fentanyl. Conclusions: This study showed that paracetamol could be an effective and safe alternative analgesic for pain control during ESWL.